The handbook of transcultural counselling and psychotherapy - Lago, Colin , 1944- (Open University Press, 2011)
"This fascinating book examines recent critical thinking and contemporary research findings in the field of transcultural counselling and psychotherapy. It also explores the effects of different cultural heritages upon potential clients and therapists. The first part of the book reflects the curriculum, context and content of counselling and psychotherapy training courses, with regards to sensitivity to diversity. It covers key issues such as: Implications of identity development for therapeutic work ; Ethnic matching of clients and therapists ; Working with interpreters and bi-cultural workers ; Overcoming racism, discrimination and oppression within the counselling process ; An overview of current research within this field. In the second part, the authors give personal accounts that explore the impact of cultural heritage on people who have moved from their countries of origin to 'Western' countries,, such as the UK or the USA. The Handbook of Transcultural Counselling and Psychotherapy will be of immense value to a wide range of readers, including counselling and therapy practitioners, supervisors, trainees, agency managers and colleagues in other therapy-related services"